Eel Kisspeptins: Identification, Functional Activity, and Inhibition on both Pituitary LH and GnRH Receptor Expression - Pasquier, Jérémy; Lafont, Anne-Gaëlle; Denis, Florian; Lefranc, Benjamin; Dubessy, Christophe; Moreno-Herrera, Antonio; Vaudry, Hubert; Leprince, Jérôme; Dufour, Sylvie; Rousseau, Karine (Frontiers in Endocrinology, 2018)
The European eel (Anguilla anguilla) presents a blockade of sexual maturation at a pre-pubertal stage due to a deficient production of gonadotropins. We previously initiated, in the eel, the investigation of the kisspeptin system, one of the major gatekeepers of puberty in mammals, and we predicted the sequence of two Kiss genes. In the present study, we cloned and sequenced Kiss1 and Kiss2 cDNAs from the eel brain. The tissue distributions of Kiss1 and Kiss2 transcripts, as investigated by qPCR, showed that both genes are primarily expressed in the eel brain and pituitary. The two 10-residue long sequences characteristic of kisspeptin, eel Kp1(10) and Kp2(10), as well as two longer sequences, predicted as mature peptides, eel Kp1(15) and Kp2(12), were synthesized and functionally analyzed. Using rat Kiss1 receptor-transfected Chinese hamster ovary cells, we found that the four synthesized eel peptides were able to induce [Ca2+]i responses, indicating their ability to bind mammalian KissR-1, and to activate second messenger pathways. In primary culture of eel pituitary cells, all four peptides were able to specifically and dose-dependently inhibit lhβ expression, without any effect on fshβ, confirming our previous data with heterologous kisspeptins. Furthermore, in this eel in vitro system, all four peptides inhibited the expression of the type 2 GnRH receptor (gnrh-r2). Our data revealed a dual inhibitory effect of homologous kisspeptins on both pituitary lhβ and gnrh-r2 expression in the European eel.